2010
DOI: 10.1016/j.jvs.2009.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol reduces restenosis after carotid artery stenting

Abstract: Although this study was retrospective and nonrandomized, the results suggest that cilostazol administration improves long-term patency after CAS due to its inhibitory effect on smooth muscle cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 37 publications
0
42
1
Order By: Relevance
“…Regarding clinical events post CAS, data were adequate for comparison in only 5 trials 16,17,19,21,22 for 30-day outcomes and in 4 trials [17][18][19]21 for outcomes during the followup period. As no heterogeneity was identified, fixed-effect models were utilized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding clinical events post CAS, data were adequate for comparison in only 5 trials 16,17,19,21,22 for 30-day outcomes and in 4 trials [17][18][19]21 for outcomes during the followup period. As no heterogeneity was identified, fixed-effect models were utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding major/minor bleeding, 3 of the studies 17,20,21 did not report any result and 2 studies 16,22 reported null bleeding events after CAS. Only one study 19 reported 7 bleedings overall (6 access site hematomas and 1 hemorrhage due to Regarding the revascularization rate post ISR, only 3 studies 18,19,22 reported a pooled rate of 33 endovascular treatments in 51 cases of ISR (65%) without stratifying the results according to antiplatelet treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Takigawa et al 7 reported a comparison of a group using CLZ (27 patients) and a group not using CLZ (70 patients) after CAS; the restenosis rate was 15.7% in the non-CLZ group with no restenosis in the CLZ group, showing a significantly greater reduction in restenosis in the CLZ group. Several different kinds of stents were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Differences in stent design and procedure appear to affect the incidence of stenosis, and the antiplatelet agent CLZ has also been reported to inhibit restenosis. 7 The aim of this study was to investigate the frequency of restenosis and the effect of CLZ in preventing such restenosis after CAS by the standard procedure using the CWS (Boston Scientific, Natick, Massachusetts).…”
mentioning
confidence: 99%
“…Cilostazol has the potential to reduce the rate of ISR after PCI 7,29) and CAS. 28,31) In this study, none of our cilostazol-treated patients manifested ISR on follow-up angiograms obtained at a mean of 5.4 months after CAS. By inhibiting the cell cycle progression of vascular smooth muscle cells (VSMC), cilostazol exerts a direct negative effect on VSMC proliferation.…”
Section: Discussionmentioning
confidence: 60%